(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bGd TjNfG GdfGFjfj(B: .. (3hGTO eG bjd aj JYQjag hGdMce HHbGA eG cGf (B.. (3bO YQahG GdGSJUMGH HJYGQja efgG JYQja GdcaGjIs
(3BNQgG (B:s
(3CNQgG(B: (3dh cGf GdMce hLhHG Ch JMQjeG hdh cGf ZjQgeG ef GdCMcGe GdJcdjajI (B... (3Ch cGf GdMce ef GdCMcGe GdhVYjI cGf GdeQLY gh ZjQgG ef GdCUhd GdLGQjI aj ehQO GdTc cd HMSHgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs